EFEKTIFITAS KONSELING SEKS USIA SENJA TERHADAP FREKUENSI HUBUNGAN SEKSUAL PADA WANITA MASA KLIMAKTERIUM - Sarwoko &; Anniez Rachmawati Musslifah Akademi Kebidanan Estu Utomo Boyolali; Universitas Sahid Surakarta (Jurnal Kebidanan, 2014)
EFEKTIFITAS KONSELING SEKS USIA SENJA TERHADAP FREKUENSI HUBUNGAN SEKSUAL PADA WANITA MASA KLIMAKTERIUM Sarwoko & Anniez Rachmawati Musslifah Akademi Kebidanan Estu Utomo Boyolali Universitas Sahid Surakarta ABSTRACT Approximately 40-85% climacteric women have sexual complaints include lost interest. This happens because the physical status of the vaginal mucosa, which must maintain adequate moisture and provide a protective lubricant during intercourse be malfunctioning, especially after menopause, atrophic changes may result in dyspareunia, vaginitis, vaginismus, physical discomfort, and loss of sexual interest (Kartono, 2007). Old age sex counseling helpful theory deal with complaints, disturbances in women during the climacteric. Sexual counseling is done to help a person identify the current condition, the matter at hand, and define the way out or attempt to resolve the issue (Saifuddin, 2002). For women the climacteric period is always important to think positive that the conditions experienced is something that is natural, as well as complaints and problems that arise in another life phase (Proverawati, 2010). This research uses the analytical survey design with a post-test only control group design, a sample of 30 respondents female climacteric period consisted of 15 respondents who received counseling group and 15 other groups who did not receive counseling in the Village District ofÂ  Boyolali Mudal Boyolali City. The results of the research data showed the majority of respondents who did not receive counseling frequency of sexual relations including minimal category, ie 13 respondents (43.33%) and the optimal 2 respondents (3.67%). While respondents who received counseling majority of sexual relationships including optimal frequency, ie 12 respondents (40%) and a minimum of 3 respondents (10%). Data analysis using SPSS version 16, the results of independent sample t-test tests the average frequency obtained sexual relationship counseling group was 1.8 in contrast to the group who did not receive counseling are 1.133 and 4.752 by t-test with p-value of 0.001 at the 5% significance level (p-value <0.05). The results of this study concluded that old age sex counseling in women during the climacteric effective against frequency of sexual intercourse than those who did not receive counseling. Keywords: sex counseling old age, frequency of sexual intercourse.